2008
DOI: 10.1364/oe.16.017420
|View full text |Cite
|
Sign up to set email alerts
|

Two-color two-dimensional Fourier transform electronic spectroscopy with a pulse-shaper

Abstract: We report two-color two-dimensional Fourier transform electronic spectroscopy obtained using an acousto-optic pulse-shaper in a pump-probe geometry. The two-color setup will facilitate the study of energy transfer between electronic transitions that are widely separated in energy. We demonstrate the method at visible wavelengths on the laser dye LDS750 in acetonitrile. We discuss phase-cycling and polarization schemes to optimize the signal-to-noise ratio in the pump-probe geometry. We also demonstrate that ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
191
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(205 citation statements)
references
References 29 publications
0
191
0
1
Order By: Relevance
“…With the advent and development of pulse-shaping technology, it is now possible to take advantage of techniques routinely used in NMR, such as phase cycling, and apply them to nonlinear optical spectroscopy (16). Here, we perform 2D optical measurements in a partially collinear geometry, the so-called pump-probe geometry, as pioneered in the mid-IR and electronic regimes by the groups of Zanni and Ogilvie, respectively (17,18) and as originally envisaged by Jonas and coworker (19). Our pulse sequence and interpulse time delays are illustrated in Fig.…”
mentioning
confidence: 99%
“…With the advent and development of pulse-shaping technology, it is now possible to take advantage of techniques routinely used in NMR, such as phase cycling, and apply them to nonlinear optical spectroscopy (16). Here, we perform 2D optical measurements in a partially collinear geometry, the so-called pump-probe geometry, as pioneered in the mid-IR and electronic regimes by the groups of Zanni and Ogilvie, respectively (17,18) and as originally envisaged by Jonas and coworker (19). Our pulse sequence and interpulse time delays are illustrated in Fig.…”
mentioning
confidence: 99%
“…In phase-cycling protocol, the desired 2D signals are retrieved by the weighted summation of data collected using different interpulse phases, φ 21 , which are cycled over 2π radians in a number of equally spaced steps. In the pump-probe configuration, Myers et al (Myers et al, 2008) have shown that other than the pure absorptive signal, the rephasing and nonrephasing contributions may also be retrieved. This phase difference detection can be defined as a two-step phase-cycling scheme.…”
Section: Multidimensional Signalsmentioning
confidence: 99%
“…If only the absorptive data is recorded, on the other hand, two pseudo Kramers-Kronig transforms along t 3 and t 1 are necessary to compute ∆D Sin [4].…”
Section: (4)mentioning
confidence: 99%
“…In the standard configuration the signals in the pump-probe configuration are inherently weaker than in a photon echo geometry, and one can access only the two polarisation tensors <XXYY> and <YYYY>, corresponding to perpendicular and parallel orientation of pump pulses and the probe and local oscillator pulse. However, it has been shown that one can amplify the 2D-IR signals by placing a polarizer in the probe beam behind the sample [3,4]. In this contribution, we manipulate the molecular response by controlling independently the polarisation of the two pump pulses as well as the probe-and the heterodyning fields.…”
Section: Introductionmentioning
confidence: 99%